Contradictions on Age of Guardianship Provisions in Marriage Law and the Compilation of Islamic Law and Its Application in Religious Courts - Rosyid, Abdur; Sa`adah, Sri Lumatus; Faisol, Muhammad (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
A child in general is someone who is not yet an adult or not married, and it is not possible for a child who is under this age to carry out legal actions by himself. For all legal actions, a child is under the authority of a guardian. The legal practice for the determination of legal guardianship for people who are Muslims according to the rules of law legislation is carried out in the Religious Court. The legal source of legal regulations regarding guardianship is regulated by Law No. 01 of 1974 concerning Marriage Chapter XI Guardianship Article 50 paragraph (1), namely the proposed child who has not reached the age of 18 years and is also regulated in Presidential Instruction No. 01 of 1991 Compilation of Islamic Law, namely in Chapter XV Guardianship Article 107 paragraph (1), namely the proposed child guardianship who has not reached the age of 21 years. The differences in legal regulations like this, create problems and do not implement the objectives of the law, namely the emergence of legal uncertainty (Contra Legal Certainty). This research uses Normative research (Normative Juridical). Namely using a statutory approach this approach is carried out by examining legislation and also an approach by examining cases or decisions of the Religious Court relating to Guardianship.